Cognitive radio networks for smart grid communications - Fang Liu; Jinkuan Wang; Yinghua Han; Peng Han (2013 9th Asian Control Conference (ASCC), 2013)
A critical component of smart grid is the integration of multiple communication technologies which can facilitate the development of smart grid. However, most of the traditional communication technologies can not satisfy the critical and complex requirements of smart grid, such as, efficiency, reliability, resilience, sustainability, and security. In this paper, the cognitive radio (CR) technology is leveraged to construct the communication infrastructure of smart grid. First, ISM bands and leased bands are introduced as backup bands to ensure the QoS of data communications in CR based networks, for which a rule that decides when to stop spectrum sensing and access the ISM bands is also provided. Furthermore, a proper communication scheme is proposed for distributed generation system based on the fact that different renewable energy source has different active period during a day. Some licensed bands whose idle time is in line with the active period of renewable energy sources are set aside exclusively for distributed generation system access. The two schemes improve both the efficiency of spectrum utilization and reliability of cognitive communications in smart grid.